Leadership Style of The Headmaster in Improving Quality of Education in SMK Al-Faqih Sumber Nyamplong Kowel Pamekasan - Abdul Halim (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2017)
The formulation of problem in this thesis research can writer describe as follows: first, how to apply principal leadership style in improving quality of education at SMK Al-Faqih Sumber Nyamplong Kowel Pamekasan? Second, How pattern of improvement of management of education quality strategy at SMK Al- Faqih Sumber Nyamplong Kowel Pamekasan? Third, how are the principal leadership style steps in improving the quality of education in SMK Al-Faqih Sumber Nyamplong Kowel Pamekasan?This research is a research that uses qualitative approach, that is research procedure that produce descriptive data in the form of written words or oral from people or behavior that can be observed. The type of this research is phenomenology, that is the researcher try to explain about the implementation field and systematic leadership style which done by the principal in improving the quality of education in SMK Al-Faqih Sumber Nyamplong Kowel Pamekasan.The research findings in this thesis can be summarized: First: The leadership style applied by the principal's leadership is a democratic leadership style, and in this case the principal applies his leadership style to the three basic patterns of duty, achieved. By using movement from button up and top down; Second: The headmaster of SMK Al-Faqih Sumber Nyamplong Kowel Pamekasan has the characteristics of spiritual leadership based on true ethics of honesty, fairness, the spirit of pious charity, the beloved leader, talk little and casual work and so on; Third: In improving the management of quality education strategy of SMK Al-Faqih Sumber Nyamplong Kowel Pamekasan principals cling to the 5 pillars of TQM, while the teachers develop management through the vision of institutional mission that is cooperation with the team, involvement stakeholders, student involvement and parental involvement.